EVALUATION OF PHOSPHOMOLYBDENUM AND FERRIC REDUCING ANTIOXIDANT POWER ASSAYS IN EXTRACT COMBINATIONS OF MANGIFERA INDICA AND EUPHORBIA HIRTA - Putra, I Made Wisnu Adhi; Suarjana, Nyoman (Walisongo Journal of Chemistry, 2025)
Combining plant extracts at lower doses may enhance antioxidant effects through synergy. This study investigated the antioxidant capacity of combined Mangifera indica and Euphorbia hirta leaf extracts using metal ion-reducing power assays. The extracts were prepared via maceration with 70% ethanol. Phytochemical profiling was conducted through preliminary screening tests. Antioxidant capacity was assessed spectrophotometrically using the phosphomolybdenum and ferric reducing antioxidant power (FRAP) assays. The phosphomolybdenum assay involved incubation of the extracts with reagent at 95°C for 90 minutes, while the FRAP assay was conducted at 37°C for 15 minutes. Extract combinations were prepared in the ratios of 1:3, 1:1, and 3:1. Phytochemical screening revealed the presence of alkaloids, phenolics, flavonoids, steroids, and terpenoids in both extracts. In the phosphomolybdenum assay, the Mo(VI) reducing power of M. indica extract (29.154±0.664 mg AAE/g extract) was higher than that of E. hirta (27.948±0.667 mg AAE/g extract). Similarly, in the FRAP assay, the ferric reducing power of M. indica extract (55.304±1.284 mg AAE/g extract) exceeded that of E. hirta (48.009±1.873 mg AAE/g extract). The highest reducing powers were observed in Comb. 3, yielding 30.745±0.715 mg AAE/g extract (phosphomolybdenum) and 57.190±1.431 mg AAE/g extract (FRAP). Among the three combinations tested, only the 3:1 ratio demonstrated a synergistic antioxidant effect in both assays.